RANCANG BANGUN DAN ANALISA PERFORMA ALAT PENUKAR PANAS DOUBLE PIPE MENGGUNAKAN METODE LMTD: SEKALA LABORATORIUM - Handik Hendratama (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2022)
A heat exchanger is a tool that is used to increase or reduce fluid temperatures. One type of this tool is a type of double pipe, this type is the simplest if compared to other types of heat exchanging devices, where hot fluid flows in the inner tube and cold fluid flows in the anulus. This study aims to analyze the efficiency of laboratory scale heat exchanging devices with water hot and cold fluids. The result shows the average effectiveness of this equipment is 20% this result is better when compared to several other studies which on the laboratory scale only show maximum efficiency at 17%. The fouling factor is an obstacle that causes a decrease in the effect of heat exchangers, the greater the fouling factor, the greater the heat resistance caused by the pipe. This study shows the amount of Fooling factor of 0.006, the value is greater than the available Fouling Factor constant. The results stated that there is a relationship between remediable numbers (Reynold numbers) with the amount of heat transferred by heat fluid. The greater the value of Reynold the greater the expressed heat. Even though it has high efficiency, this equipment can still not be used because of some considerations such as low efficiency and efficient..